2015
DOI: 10.1176/appi.ps.201500134
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Criminal Justice Involvement and Psychiatric Diagnoses on Treatment Costs Among Adults With Serious Mental Illness

Abstract: The impact of criminal justice involvement and clinical characteristics on the cost of public treatment services for adults with serious mental illnesses is unknown. The authors examined differential effects of justice involvement on behavioral health treatment costs by primary psychiatric diagnosis (schizophrenia or bipolar disorder) and also by substance use diagnosis among 25,133 adult clients of Connecticut’s public behavioral health system in fiscal years 2006 and 2007. Justice-involved adults with schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…This finding is consistent with previous research (Clark, Ricketts, & McHugo, 1999;Theriot & Segal, 2005). In a state study of 25,133 adults, it was found that 27% over a two-year period were involved with the criminal justice system in some way (Robertson et al, 2015). Furthermore, 37% were diagnosed with schizophrenia and 65% were diagnosed with a co-occurring substance abuse disorder.…”
Section: Substance Abusesupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous research (Clark, Ricketts, & McHugo, 1999;Theriot & Segal, 2005). In a state study of 25,133 adults, it was found that 27% over a two-year period were involved with the criminal justice system in some way (Robertson et al, 2015). Furthermore, 37% were diagnosed with schizophrenia and 65% were diagnosed with a co-occurring substance abuse disorder.…”
Section: Substance Abusesupporting
confidence: 91%
“…In one study, it was found that individuals diagnosed with schizophrenia who were involved with the criminal justice system cost the state 70% more at US$61,824 than those diagnosed with schizophrenia without criminal justice system involvement at US$36,408 (Robertson et al, 2015). It was concluded that the higher cost is attributed to forensic hospitalizations largely emanating from being found incompetent to stand trial and being found not guilty by reason of insanity (Robertson et al, 2015) In summary, based upon a discussion of empirically-derived antecedents, it must be stated that the prediction of violence among persons with schizophrenia is challenging. Given the previously-discussed reality that few persons with schizophrenia exhibit violent behaviour (Fazel et al, 2009), it has been asserted that any process to predict violent behaviour may result in false positives (Szmukler, 2001).…”
Section: Competent To Stand Trialmentioning
confidence: 99%
“…We will also interview 4 peer navigators working with prisons from other states to understand experiences across the country using the topic guide described above. With potential client groups, we will explore (1) how peer navigators can best gain their trust; (2) their greatest needs in overcoming barriers to (postrelease) treatment engagement, (3) what would assist their treatment engagement and how peer navigators could help with that, and (4) feedback on the proposed MAPS intervention outline. To understand the challenges after re-entry, we will include participants who have had re-entry experiences.…”
Section: Current Contentsmentioning
confidence: 99%
“…Approximately 12 million people in the U.S. become or are incarcerated each year. Among these, individuals with serious mental illnesses (SMI; psychotic and affective disorders associated with functional impairment and interference with major life activities) are disproportionately represented, accounting for 25% of the justice-involved population [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Calculate the effect size and 95% CI separately for number of outpatient substance use appointments and number of outpatient medical appointments. (3) Conduct an exploratory comparison of the number of days between jail release and the rst outpatient mental health appointment using Cox regression.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%